2016
DOI: 10.1515/jpem-2016-0098
|View full text |Cite
|
Sign up to set email alerts
|

Referral pattern of children with short stature to a pediatric endocrine clinic in Kuwait

Abstract: Our study highlights the need to improve the referral process in order to avoid unnecessary investigations and alleviate parental anxiety. There is no gender bias in short stature referrals in Kuwait. There is a need of further investigation of short stature in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Short stature is one of the most common reasons for referrals to pediatric endocrinologists (3,9). However, a retrospective review of children with short stature referred to a pediatric endocrinologist at an endocrine clinic in Kuwait found that approximately one-fifth of referred children had normal growth (9). This observation suggests that there is a need to improve the referral process so that unnecessary investigations and parental anxiety are avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Short stature is one of the most common reasons for referrals to pediatric endocrinologists (3,9). However, a retrospective review of children with short stature referred to a pediatric endocrinologist at an endocrine clinic in Kuwait found that approximately one-fifth of referred children had normal growth (9). This observation suggests that there is a need to improve the referral process so that unnecessary investigations and parental anxiety are avoided.…”
Section: Introductionmentioning
confidence: 99%